Web-Based Geographic Information System for Mapping and Spatial Visualization of Cultural and Historical Tourism Objects in Makassar City - Aulia, Hafiz; Elvianti, Dedek (SYNAPSI: Journal of Information Systems and Informatics Education, 2026)
Purpose of the study: This research aims to develop a web-based Geographic Information System (GIS) for mapping and visualizing the spatial distribution of cultural and historical tourism objects in Makassar City, integrating location coordinates, access routes, and descriptive information into an interactive digital platform accessible to the public and stakeholders.Methodology: This study employed a descriptive qualitative method with a system development approach. The research stages included planning, data collection through interviews and observations at the Makassar City Culture and Tourism Office, and system development using ArcView 3.3 for map digitization, ALOV Map v.096 as the WebGIS framework, PHP programming language, and MySQL database. Black-box testing was conducted to evaluate system functionality and interface performance.Main Findings: The research successfully produced a web-based GIS application displaying 20 cultural and historical tourism sites across Makassar City, complete with coordinate points and descriptive information. The system integrates supporting spatial data including 14 sub-district boundaries, 143 urban village boundaries, 20 main roads, and river networks, all accessible through an interactive map interface with navigation features and query capabilities. Black-box testing confirmed all system functions operated as expected.Novelty/Originality of this study: This study presents the first integrated WebGIS specifically designed for Makassar's cultural heritage that combines multi-layer spatial data with dynamic content management capabilities, effectively.